PERBEDAAN PENGARUH ABDOMINAL STRETCHING EXERCISE DENGAN KOMPRES HANGAT TERHADAP PENURUNAN NYERI HAID PADA REMAJA DI SMA SINGOSARI DELI TUA - Hutabarat, Vitrilina -; Sitepu, Stefani Anastasia; Herdiana, Herdiana (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2025)
Bacground : Menstrual pain is pain that occurs during menstruation, usually accompanied by cramps in the lower abdominal area. This pain can appear before menstruation, during menstruation, until the end of menstruation, until the end of menstruation, with an intensity that can come and go or continue without stopping. This study aims to identify the differences in the effect of abdominal stretching exercise with warm compresses on reducing menstrual pain in Singosari Deli Tua High School in 2025. Method : The design this study uses a quasi-experimental design method with a two-group pre test-post test group design. The population in this study were all teenagers in SMA Singosari Deli Tua with a total of 20 respondents, by using purposive sampling.The researcher divided respondents into two groups. Data were analyzed using the Paired T-Test and Independent T-Test. Research Result : The result of this study was indicate that based on statistical test using the Paired T-Test, Abdominal Stretching Exercise on group I with p- value = 0.000 and Warm Compress on group II with p-value = 0.015 which means there is a significant difference between the average pain scale pre-test and post-test, while the Independent T-Test between Abdominal tbat there is a significant difference between Abdominal Stretching Exercise and Warm Compress show significant differece with p-value = 0.04 (p > α; α = 0.05). Conclusion : It was observed that Abdominal Stretching Exercise and Warm Compresses can reduce the scale of menstrual pain and when comparing the Abdominal Stretching Exercise and Warm Compresses, significant differences to reduce the scale of menstrual pain , so these two interventions are equally effective in reducing the scale of menstrual pain. Therefore,the study recommend to use one of the intervention to reduce menstrual pain